A forensic case study for body fluid identification using DNA methylation analysis. (July 2021) - Choung, Chong Min; Lee, Jee Won; Park, Ji Hye; Kim, Cho Hee; Park, Hyun-Chul; Lim, Si-Keun
Highlights: Applying of the DNA methylation for body fluid identification in forensic field samples. DNA methyl profiles from the saliva, semen, blood, menstrual blood, vaginal fluid. Mixed body fluids were identified simultanuously by DNA methylation analysis. Abstract: Recently, a method of identifying body fluids using DNA methylation has been developed (Frumkin et al., 2011). An existing multiplex assay using 9 CpG markers could differentiate 5 body fluids: semen, blood, saliva, menstrual blood, and vaginal fluid. To validate this technique, we evaluated the previously described body fluid identification method by means of single base extension (SBE). DNA methylation was applied to 22 samples in 18 forensic cases; seven of these were semen, three were blood, eight were saliva, three were vaginal fluid, and one was menstrual blood. Total of 18 samples were tested, the DNA methylation profiles were coincident from preliminary tests (acid phosphatase (AP), leucomalachite green (LMG, Sigma Aldrich, St Louis, MO, USA) and SALIgAE®) except one sample which displayed an all-negative result. After applying the DNA methylation method to forensic samples, we determined that it could be very useful for differentiating vaginal secretions from menstrual blood, for which there is no conventional preliminary testing method.